Effect of Gamma Irradiation on Some Biochemical Components of Seed Extracts and Microbial Load of Fenugreek (Trigonella foenum-graecum L.) Seeds* (University of Khartoum Journal of Agricultural Sciences, 2023)
The work was carried out to study the effects of gammairradiation on microbial load and the content of some biochemicalconstituents of fenugreek (Trigonella foenum-graecum) seeds. It wasconducted at the Department of Botany and Agricultural Biotechnology,Faculty of Agriculture, University of Khartoum and Institute of Botany,Technische Universität Dresden. Seeds were treated with gammairradiation at the doses of 5, 10 and 15 kGy. Bacterial load was reducedfrom 1.44 x 106 , in untreated seeds, to 1.5 x 104 , 9.0 x 103 and 5.0 x 102cfu/g, in seeds treated with5, 10 and 15 kGy, respectively. The stability ofglycosides, phenols and tannins constituents of treated seeds wasevaluated using thin layer chromatography (TLC) and high performanceliquid chromatography (HPLC). The results of TLC analysis revealed thatapplication of 15 kGy doses of gamma radiation to fenugreek seedsmethanol-extract had no effect on glycosides patterns, and slightreduction in total phenol and increase in tannins content were observed.Analysis of methanol extractable compounds by HPLC revealedvariations in the metabolite profile at different wavelengths afterirradiation. While the content of several compounds increased slightlyafter gamma irradiation that of some decreased and some constituentsshowed no change. Accordingly, there were no major differences inchemical constituents between the irradiated and un-irradiated samples.